2012
DOI: 10.1016/j.amjcard.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Cholesterol Efflux, Nitration of Apolipoprotein A-I, and Endothelial Function in Obese Women

Abstract: Subjects at risk for atherosclerosis may have dysfunctional high-density lipoprotein (HDL) despite normal cholesterol content in plasma. We considered whether efflux of excess cellular cholesterol to HDL from obese subjects is associated with impaired arterial endothelial function, a biomarker of cardiovascular risk. Fifty-four overweight (body mass index [BMI] 25 – 29.9 kg/m2) or obese women (BMI ≥ 30 kg/m2), age 46 ± 11 years, were enrolled in a worksite wellness program. HDL cholesterol averaged 57 ± 17 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In addition, in a population of healthy subjects, ABCA1-mediated serum CEC was inversely correlated with pulse wave velocity, an index of arterial stiffness, independent of HDL-C serum levels (Favari et al 2013). A work measuring the flow-mediated dilation, as a parameter of endothelial function, showed a positive correlation with the ABCA1-mediated efflux pathway confirming the concept that the functional measures of HDL might be a better marker for cardiovascular risk rather than HDL cholesterol levels (Vazquez et al 2012). Recently, Li and colleagues provided data indicating that individuals in the top tertile of CEC had a moderately increased risk of a composite cardiovascular end point of incident myocardial infarction, stroke, or death during 3 years of follow-up (Li et al 2013).…”
Section: Serum Cholesterol Efflux Capacity (Cec)mentioning
confidence: 62%
“…In addition, in a population of healthy subjects, ABCA1-mediated serum CEC was inversely correlated with pulse wave velocity, an index of arterial stiffness, independent of HDL-C serum levels (Favari et al 2013). A work measuring the flow-mediated dilation, as a parameter of endothelial function, showed a positive correlation with the ABCA1-mediated efflux pathway confirming the concept that the functional measures of HDL might be a better marker for cardiovascular risk rather than HDL cholesterol levels (Vazquez et al 2012). Recently, Li and colleagues provided data indicating that individuals in the top tertile of CEC had a moderately increased risk of a composite cardiovascular end point of incident myocardial infarction, stroke, or death during 3 years of follow-up (Li et al 2013).…”
Section: Serum Cholesterol Efflux Capacity (Cec)mentioning
confidence: 62%
“…41 The reason why cholesterol might relate to PVS in SLE is unknown and could be spurious given our study’s lack of power, but HDL can become dysfunctional resulting in inflammation 42,43 and endothelial dysfunction. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Although there appears to be a tendency towards higher plasma NT-apoAI levels in diabetes and CAD subjects, the studies were small and used gas chromatography-mass spectrometry methods that are not suitable for larger cohort studies. Previously, we developed a novel 20 enzyme-linked immunosorbent assay (ELISA), which was confirmed by both Western blot analysis 20 and mass spectrometry 19 . This sensitive and specific ELISA method is suitable to quantify human NT-apoAI levels in a large population.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, higher levels of NT-apoAI were found in patients with cardiovascular disease in both the circulation and in atheroma 13, 14, 16 . Recently, Vazquez et al reported a significantly higher level of circulating NT-apoAI in obese women 19 . Although there appears to be a tendency towards higher plasma NT-apoAI levels in diabetes and CAD subjects, the studies were small and used gas chromatography-mass spectrometry methods that are not suitable for larger cohort studies.…”
Section: Introductionmentioning
confidence: 97%